The relationship between health services and food intake with the incidence of chronic energy deficiency in pregnant women - Wiwin Astry Pasaribu; Asparian Asparian; Ashar Nuzulul Putra; Muhammad Syukri (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Malnutrition in pregnant women is a global health problem that accounts for about 7% of the world's disease burden and contributes to more than 20% of maternal deaths. The WHO estimates that 35–40% of pregnant women in developing countries are at risk of mild to moderate KEK, which leads to an increase in MMR and newborn deaths. Purpose: To analyze the relationship between health services and food intake with chronic energy deficiency (CED) in pregnant women. Method: This study used an analytical observational design with a case-control approach. The sample consisted of 44 people, comprising 11 case samples and 33 control samples. Data were collected through interviews using questionnaires and analyzed using path analysis. Result: There is a significant relationship between health services (p = 0.000) and food intake (p = 0.001) with chronic energy deficiency in pregnant women. Conclusion: This study concluded that there is a relationship between health services and food intake with chronic energy deficiency in pregnant women in the Kenali Besar Community Health Center area of Jambi City in 2025. Suggestion: Pregnant women are expected to pay more attention to fulfilling their nutritional intake during pregnancy and make optimal use of health services such as regular antenatal care (ANC) visits.